Discovery of spectacular quasar-driven superbubbles in red quasars - Shen, Lu; Liu, Guilin; He, Zhicheng; Zakamska, Nadia L.; Glikman, Eilat; Greene, Jenny E.; Hu, Weida; Mou, Guobin; Wylezalek, Dominika; Rupke, David S. N. (Science advances, 2023)
Quasar-driven outflows on galactic scales are a routinely invoked ingredient for galaxy formation models. We report the discovery of ionized gas nebulae surrounding three luminous red quasars at z ~ 0.4 from Gemini integral field unit observations. All these nebulae feature unprecedented pairs of “superbubbles” extending ~20 kpc in diameter, and the line-of-sight velocity difference between the red- and blueshifted bubbles reaches up to ~1200 km/s. Their spectacular dual-bubble morphology (in analogy to the galactic “Fermi bubbles”) and their kinematics provide unambiguous evidence for galaxy-wide quasar-driven outflows, in parallel with the quasi-spherical outflows similar in size from luminous type 1 and type 2 quasars at concordant redshift. These bubble pairs manifest themselves as a signpost of the short-lived superbubble “break-out” phase, when the quasar wind drives the bubbles to escape the confinement from the dense environment and plunge into the galactic halo with a high-velocity expansion.
Online veröffentlicht: 12. Juli 2023
Gesehen am 09.10.2023